GAMBARAN KARAKTERISTIK WANITA USIA SUBUR MELAKUKAN PEMERIKSAAN CLINICAL BREAST EXAMINATION (CBE) (Studi di Puskesmas Parakan Kabupaten Temanggung) - Ida Mahfiroh; Ari Udiyono; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Breast tumor is a neoplasm or abnormal lump on breast, and the main cause of women’s death. The purpose of this study is to know the description of characteristics of women of fertile age who do breast tumor examination (CBE) in Puskesmas Parakan. This study was a descriptive study with cross sectional study approach. The number of population of this research is 9.314 women aged 20-60 years in Parakan Puskesmas,while the number of samples is 120 women. Results of this research show that women who doing breast examination at most widely in the age range 41-45 years (23,3%) with a age mean of 39 years, graduated from secondary school (35.8%) with a job as a housewife (34.2%) and the highest percentage parity was responden that have two children(45,8%). Conclusion the characteristics of respondents who doing breast tumors examination in women with older age range, secondary education and have some free time at home. Therefore, need for healthcare provider to provide counseling to young women who are working to be active to doing breast tumor examination.